The dynamics of drug resistance evolution and diagnosis in Mycobacterium tuberculosis : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Genetics/Genomics, Massey University, Manawatu, New Zealand - Fong, Yang (Richard) (Massey University, 2024)
Tuberculosis (TB) remains a critical global health challenge with over 10.4 million new cases annually, complicated by rising antimicrobial resistance (AMR) threatening to surpass cancer mortality by 2050. This PhD thesis establishes a systematic diagnostic framework addressing AMR challenges through progressive research from fundamental microbiome characterization to innovative diagnostic applications in resource-limited settings like Myanmar. The "Microbiome Dataset from the Upper Respiratory Tract of Patients Living with HIV, HIV/TB and TB from Myanmar" establishes the foundational understanding of microbial community structures in complex clinical presentations (n=309 isolates). This microbiome characterization reveals critical signatures that directly inform direct sequencing strategies for enhanced MTBC detection in polymicrobial environments, addressing a fundamental challenge in AMR detection. Next, the "Genomic Profiling of Mycobacterium tuberculosis Strains, Myanmar" validates and expands these microbiome-informed approaches through comprehensive whole genome sequencing surveillance, establishing genotype-phenotype correlations that achieve 97.8% concordance with phenotypic testing. This genomic profiling directly addresses AMR surveillance gaps by enabling rapid resistance prediction. Subsequently by "Unveiling Hr-TB in Myanmar: Comprehensive Genotypic and Phenotypic Insights for Improved TB Management" demonstrates targeted application of microbiome-informed diagnostic approaches to isoniazid mono-resistant TB, a clinically critical AMR variant frequently missed by conventional methods. The integrated microbiome-genomic approach enhances MTBC detection accuracy by 23% compared to standard methods, reducing diagnostic time from weeks to under one week. Future perspectives translate these discoveries into field-deployable MDA primer systems for point-of-care AMR detection using portable MinION sequencing technology. This systematic progression from microbiome foundation to diagnostic innovation establishes a replicable technological blueprint for next-generation TB AMR diagnostics, supporting Myanmar's National TB Control Program while providing a framework for global TB elimination efforts Keywords: Mycobacterium tuberculosis (MTB), Tuberculosis (TB), Antimicrobial Resistance (AMR), Isoniazid Mono-Resistant (Hr-TB), Drug-Resistant Tuberculosis (DR-TB), Whole-genome sequencing (WGS), Resistance associated Mutations, Epidemiology, Surveillance, Rapid Diagnosis, Microbiome, Yangon, Myanmar.
Keywords: biological science, biochemistry, microbiology, bioinformatics, medical diagnosis, epidemiology, public health, tuberculosis, antimicrobial resistance, whole-genome sequencing, next generation sequencing; Mycobacterium tuberculosis; Drug resistance in microorganisms; Tuberculosis; Myanmar; Case studies; Microbiology; Diagnosis; 310509 Genomics; 310704 Microbial genetics